2022
DOI: 10.7759/cureus.22346
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlation and Role of Cyclin D1 Expression in Glioblastoma Patients: A Study From North India

Abstract: Background/Aims Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor. Cyclin D1 is a protein that in humans is encoded by the CCND1 gene. Cyclin D1 protein is frequently overexpressed in malignant gliomas. Methods It is an observational study comprising 40 biopsy-proven cases of GBM in a span of one and half years. Immunohistochemistry (IHC) was used with Cyclin D1 monoclonal antibody. Cyclin D1 on the outcome was assessed using the Kaplan-Meier survival est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Cyclin D1 binds to cyclin-dependent kinase 4 and 6, activating the G1/S transition. High expression of Cyclin D1 is associated with the pathological grade and proliferative activity of astrocytomas [27,28]. Overexpression of Cyclin D1 induces TMZ resistance by upregulating P-gp in human malignant glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 binds to cyclin-dependent kinase 4 and 6, activating the G1/S transition. High expression of Cyclin D1 is associated with the pathological grade and proliferative activity of astrocytomas [27,28]. Overexpression of Cyclin D1 induces TMZ resistance by upregulating P-gp in human malignant glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the proposed cancer-related case studies consistently enrich a small cluster of oncology-related pathways like Aberrant regulations of the mitotic cell cycle (R-HSA-9687139 and its sub-pathways). Interestingly, a set of pathways linked to cell cycle like Cyclin D associated events in G1 (R-HSA-69231) are enriched in the oligodendrocyte case study and reported to be also relevant in glioblastoma (53)(54)(55)(56). We included a positive control case study as we expected that a co-occurrence network derived from a highly heterogenous corpus should possess little context specificity.…”
Section: Enquire's Network Improve the Context Resolution Of Topology...mentioning
confidence: 99%
“…Similarly, some of Chromatin Organization and Developmental Biology pathways are almost exclusively enriched in the networks corresponding to oligodendrocyte differentiation. Interestingly, a set of pathways linked to cell cycle like Cyclin D associated events in G1 (R-HSA-69231) are enriched in the oligodendrocyte case study and reported to be also relevant in glioblastoma [41][42][43][44] . All case studies appear constitutively enriched in a cluster of Pathways in Cancer annotated downstream of Diseases of signal transduction by growth factor receptors and second messengers (R-HSA-5663202).…”
Section: Enquire Improves the Context Resolution Of Topology-based Pa...mentioning
confidence: 99%